PENGARUH LINGKUNGAN KELUARGA, PENGALAMAN BELAJAR MICRO TEACHING DAN PRESTISE PROFESI GURU TERHADAP MOTIVASI MENJADI GURU - Vidi Tanoyo; Lilik Sri Hariani; Udik Yudiono (Jurnal Riset Pendidikan Ekonomi, 2017)
The purpose of this study was to determine : 1) Whether there is any influence between family environment, learning experience in microteaching, and prestige of the teaching profession on motivation to be a teacher, 2) Whether there is influence of family environment on motivation to be a teacher, 3) Whether there is influence of learning experience in microteaching on motivation to be a teacher , 4) Whether there is influence of prestige of the teaching profession on motivation to be a teacher. This research use quatitative study. The methods that use on this reseach is multiple linier regression. The study sample of 52 student Economic Education. The result of this study are as follow : 1) There is influence between family environment, learning experience in microteaching, and prestige of the teaching profession on motivation to be a teacher, 2) There is a significant effect of family environment on motivation to be a teacher, 2) There is a significant effect of learning experience in microteaching on motivation to be a teacher, 3) There is a significant effect of prestige of the teaching profession on motivation to be a teacher